The pen and the cross in Franco’s service: Alfonso Junco and the Spanish Republican Exile in Mexico (Tzintzun, Revista de Estudios Históricos, 2016)
Ater the Civil War of 1936, the Mexican writer and journalist Alfonso Juncowas one of the supporters of not only General Franco’s crusades against therepublican bloc, but also of the decision of sending them to exile overseasto the “other Spain”, a decision which was carried out ater the conlict. Afervent defender of the cross and a detractor of ideologies such of liberalism,communism and even fascism, Alfonso Junco strongly criticized the arrivalof Spanish refugees to Mexico, with the intention of undermining the ideologicaland institutional project which would end up in forming the SpanishRepublican government in exile through the institutional reconstruction ofMexico City in August 1945. Disputes between Indalecio Prieto and Juan Negrín,the Project of Morelia’s children or the confusing issue on the treasuresof Vita were topics that intensiied Junco’s criticism against the Spanish inexile.
Keywords: Alfonso Junco; Republican Exile; Franco regime; Indalecio Prieto; Juan Negrín; “oro del exilio”